Functional, Antioxidant, Antibacterial, and Antifungal Activity of Edible Flowers - Elena Coyago-Cruz; Alejandro Alarcón; Aida Guachamin; Gabriela Méndez; Edison Osorio; Jorge Heredia-Moya; Johana Zuñiga-Miranda; Elena Beltrán-Sinchiguano; Edwin Vera (MDPI AG, 2024)
Edible flowers have been used since ancient times, but their potential for improving human health has not been explored. This study aimed to evaluate the profile of bioactive compounds (organic acids, phenolics, and carotenoids) and the antioxidant and antimicrobial activity of nine flower varieties with high concentrations of carotenoids or total phenolic compounds. Ninety-three edible flowers were analysed for physicochemical characteristics, total phenolic and carotenoid concentrations, and antioxidant activity (ABTS). Bioactive profiles were determined by rapid resolution liquid chromatography (RRLC), and antimicrobial activity was determined against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Streptococcus mutans, and Candida albicans and Candida tropicalis. Chrysanthemum x hybrid orange, Helianthus annuus yellow, Tagetes patula orange, Canna indica red, and Hibiscus rosa-sinensis (orange1 and yellow) showed significant concentrations of total carotenoids. In contrast, Pelargonium hortorum orange2, Hibiscus rosa-sinensis red1, and Rosa x hybrid variety medium yellow showed high levels of total phenolics. The predominant compounds in these species were citric acid (991.4 mg/g DW in Hibiscus rosa-sinensis red1), 4-hydroxybenzoic acid (936.2 mg/100 g DW in P. hortorum orange2), kaempferol (971. 9 mg/100 g DW in T. patula orange), quercetin glucoside (958.8 in C. x hybrid), quercetin (919.3 mg/100 g DW in T. patula), α-carotene, and β-carotene in T. patula orange (989.5 and 601.2 mg/100 g DW, respectively). Regarding antimicrobial activity, T. patula orange and P. hortorum orange2 inhibited bacterial growth, while C. x hybrid orange and P. hortorum orange2 inhibited Candida albicans, and the latter inhibited Candida tropicalis. These results indicate the potential of edible flowers as a natural source of bioactive compounds and as a tool in the fight against antimicrobial resistance.